Survival of Mycobacterium avium subspecies paratuberculosis in retail pasteurised milk - Gerrard, Zara E.; Swift, Benjamin M.C.; Botsaris, George; Davidson, Ross S.; Hutchings, Michael R.; Huxley, Jonathon N.; Rees, Catherine E.D. (Elsevier, 2018)
A survey of retail purchased semi-skimmed pasteurised milk (n = 368) for Mycobacterium avium subspecies paratuberculosis (MAP) was conducted between May 2014 and June 2015 across the midlands of England using the Phage-PCR assay. Overall, 10.3% of the total samples collected contained viable MAP cells, confirming that pasteurisation is not capable of fully eliminating human exposure to viable MAP through milk. Comparison of the results gained using the Phage-PCR assay with the results of surveys using either culture or direct PCR suggest that the phage-PCR assay is able to detect lower numbers of cells, resulting in an increase in the number of MAP-positive samples detected. Comparison of viable count and levels of MAP detected in bulk milk samples suggest that MAP is not primarily introduced into the milk by faecal contamination but rather are shed directly into the milk within the udder. In addition results detected an asymmetric distribution of MAP exists in the milk matrix prior to somatic cell lysis, indicating that the bacterial cells in naturally contaminated milk are clustered together and may primarily be located within somatic cells. These latter two results lead to the hypothesis that intracellular MAP within the somatic cells may be protected against heat inactivation during pasteurisation, accounting for the presence of low levels of MAP detected in retail milk.